LA FIJACION DE OBJETIVOS EN LA DOCENCIA UNIVERSITARIA DE DISCIPLINAS ADMINISTRATIVAS: UN COMENTARIO - Verona Martel, María Concepción (2005)
The purpose of this paper is to show the importance of the objectives on the educationlearning process, with a special reference to the university teaching of the administrative disciplines. Likewise, we emphasize the importance of the existence of a narrow relation among University, society and firm.